Party centralisation, internal cohesion and leadership security: How UK prime ministers compare to Japanese prime ministers. Issue 1 (March 2023) - Heppell, Timothy
This article considers UK prime ministers as leaders of their political parties. It evaluates the extent to which the three trends identified by Uchiyama in this issue, in relation to Japanese prime ministers, are replicated in the case of UK prime ministers. First, to what extent is the Japanese trend towards increasing party centralisation replicated within the UK Labour and Conservative parties? Second, to what extent is the Japanese trend of reduced factional influence and lower rebellion rates replicated in the case of the UK Labour and Conservative parties? Finally, is the association between leadership personalisation and party leadership security – i.e. how an approval rating of below 30 per cent will act as a trigger for the removal of an incumbent Japanese prime minister – replicated in the case of the UK Labour and Conservative parties?